The effects of biofeedback‐based stimulated recall on self‐regulated online learning: A gender and cognitive taxonomy perspective. (10th July 2018) - Zhai, Xuesong; Fang, Qiansheng; Dong, Yan; Wei, Zhihui; Yuan, Jing; Cacciolatti, Luca; Yang, Yalong
Abstract: Previous studies posited the effectiveness of stimulated recall. However, few studies explored how SR is implemented in a relatively static context, for example, online self‐directed learning, or took human factors, for example, cognitive style and gender, into consideration in such a context. To fill this gap, the current study, aims to introduce biofeedback as a stimulus for learners to engage in retrospection regarding their learning behavior. A quasi‐experimental design study was carried out over a 12‐week set of EFL self‐regulated online reading activities. Pretest and posttest on reading performance and their cognitive taxonomy were assessed through a developed scale instrument, whereasphysiological signal s (e.g., gazing duration, verbal fixation, and brain wave) were captured via eye‐tracking and electroencephalograph (EEG) technology. The results emphasized that (a) students' reading ability and cognitive hierarchy significantly improved through biofeedback stimulation. Moreover, (b) learners in single level‐one cognitive hierarchic groups had significant improvements in both cognitive abilities and reading comprehension, whereas learners in multilevel hierarchic groups had no significant enhancements. Finally, (c) the optical data results and EEG reports showed that males favor procedural feedback and females have a preference for a conclusive assessment. Lay Description: What is already known about this topic: ·The stimulated recall (SR) technique, considered being a valuable tool for learners to capitalize on introspection, has positive effect on learning outcomes and cognitive processes in physical context. The recorded audio and video are generally used as the stimulus in physical learning context. The stimulus source may differ from a research context to another. Learning performance has close relationship with different human factors, such as cognitive taxonomy and gender differences. What this paper adds: Students adopting the biofeedback as stimulus demonstrated significant improvement in the dimensions of cognitive level and reading comprehension. Biofeedback, such as EEG and eye movement, may be applicable stimulus for stimulated recall in online self‐directed learning context. The lower cognitive students have more significant enhancement of taxonomy and reading capacity, when conducting biofeedback‐based stimulated recall. Eye‐track reports showed that males favor procedural feedback and females have a preference for the conclusive assessment. Implications for practice and/or policy: Biofeedback may act as a meta‐cognitive method to help learners realize their personalized learning habits and cognitive modes and encourage them to embark in the often daunting journey of autonomous learning. Biofeedback data could be used as valuable measurements for instructors to adjust their pedagogic design and improve teaching arrangements according to learners' emotional status and human factors. Procedural feedback is adaptive and should be considered utilizing for male students in self‐access learning context, whereas conclusive assessment approach is more applicable for female learners.